Is dualism still a source of convergence in Europe? - Raffaele Paci; Francesco Pigliaru (European Regional Science Association (ERSA), 1998)
This paper aims at assessing whether dualistic mechanisms represent a significant component of the aggregate labour productivity convergence observed across the European regions in the 1980s. The potential of an explanation of convergence based - in part, at least - on the existence of dualism in some of the initially poorer regions has been largely ignored by the literature. We use a dualistic model based on Dixit (1970) and on Mas-Colell and Razin (1973) to obtain hypotheses to be tested in cross-region growth regressions. In particular, we wish to test whether a high initial allocation of labour in agriculture in fact generates – in each sector as well as at the aggregate level – the specific impact on productivity growth (and therefore on convergence) implied by the theory of the dual economy. We use the data-base Regio-Eu set up by CRENoS, with aggregate and sectoral data for 109 territorial units from 1980 to 1990. Our cross-section results are consistent with the major predictions of the dualistic model. While part of the influence exerted by dualistic mechanisms is not easily distinguishable from the one exerted by other mechanisms such as technology diffusion, still the former appears to be a significant component of the whole process of convergence. Ignoring such component could lead to misleading interpretations of the relative roles played by each of the forces behind the process, and to inexact assessments of what actions should be taken - if any - by the European regional policy to help the process become more pervasive. Keywords: Dualism, Growth, Convergence, Regions, Europe JEL: O40, O41, O52, R11
Keywords: 330